Inclusive educational practices in Latin America: conceptualization, types, and characteristics. A systematic review: Inclusive educational practices in Latin America: conceptualization, types, and characteristics. A systematic review - Conejeros-Solar, María Leonor; Rojas Farías, Ana; Melo-Letelier, Giselle (Revista Complutense de Educación, 2026)
Introduction: Educational practices are key to promoting the inclusion of all students in the school system, based on principles of equity and universal access. Their interpretation and execution depend on contextual and intersubjective factors, which adds complexity to their implementation. Although there is an extensive literature on inclusive practices, a gap persists regarding their conceptualization and the characteristics of the practices applied. Method: This systematic review has two objectives: to analyze the conceptual frameworks of inclusive educational practices and to identify the types of practices implemented and their characteristics as reported in recent academic works. Following PRISMA guidelines, articles indexed in SCOPUS, WoS and SciELO databases were reviewed, focusing on publications from 2021 to 2023. The selection process included rigorous inclusion and exclusion criteria, resulting in the analysis of 29 articles. The methodology included a content analysis to extract and synthesize information relevant to the study objectives. Results: The findings reveal a diversity of definitions, types, and characteristics of inclusive educational practices ranging from diversified teaching strategies and collaborative learning among students to culturally responsive teaching and collaborative work among professionals. These findings highlight the diverse approaches educators employ to create inclusive environments, reflecting the complex interplay of educational policies, cultural contexts, and educators' individual philosophies. Discussion: The importance of understanding the complex and nuanced nature of inclusive practices, as well as their application in diverse educational contexts, is highlighted. This highlights the need to adapt such practices to the changing needs of students in an increasingly globalized world. Although definitions may vary, developments in this area have contributed significantly to promoting inclusion within educational communities.
Keywords: inclusive education; teaching practice; school environment; students; teachers